Diabetic Ketoacidosis associated with Steroid in a Renal Transplant Recipient - Şimal Köksal Cevher; Ezgi Çoşkun Yenigün; Nihal Özkayar; Nergiz Bayrakcı; Fatih Dede (İstanbul Medical Journal, 2015)

(untitled)
Post-transplant diabetes mellitus is a serious complication of organ transplantation. Post-transplant diabetes mellitus is a form of type 2 diabetes mellitus that is thought to develop in response to a relative insulin deficiency resulting from increased insulin resistance or impaired insulin production or a combination of both. The clinical presentation varies from asymptomatic hyperglycemia to hyperosmolar dehydration or diabetic ketoacidosis. The onset of diabetes is associated with reduced graft function and patient survival. Immunosuppressive drugs, such as corticosteroids and calcineurin inhibitors (cyclosporine and tacrolimus), are known to be diabetogenic. However, the association of diabetic ketoacidosis with the use of systemic corticosteroids is infrequently reported. Here, we report a 27-year-old female recipient of a live renal transplant who developed diabetic ketoacidosis associated with short-term corticosteroid treatment.